MENSTURAL DISORDERS IN MONOPHASIC AND TRIPHASIC ORAL CONTRACEPTIVE USERS - Kh. Safavi; S.M. Zyadlou (Iran University of Medical Sciences, 2004)
Oral Contraceptive Pill (OCP) is usually prescribed in the form of a combined estrogen and progesterone tablet. The combined pill can be presented as a monophasic pill in which the dose of both hormones is constant throughout the cycle. There is also a triphasic form in which the doses of the hormones vary three times. This form is thought to mimic the natural cycle more closely than other types and usually has a slightly lower overall dose of hormones. As with every medication there are potential side effects of the OCP, one of which is menstrual disorders.   Comparing the side effects of two mentioned products, we carried out a descriptive study and 188 participants were assigned in two groups of 92 users of monophasic whereas, the rest were on triphasic drug.   Our findings revealed that both drugs had the capability to decrease the amount of bleeding, the duration of the cycle and the intensity of dysmenorrhea. We did not find significant increase in spotting with triphasic drug, or any bleeding or/and amenorrhea with both drugs.   To sum up, there is not any difference between the side effects of both drugs, and monophasic product can be compensated with triphasic one.